Growth performance, waste reduction and efficiency of conversion of digested food waste by Hermetia illucens larvae via bioconversion - Kutty, S.R.M. (Journal of Pure and Applied Microbiology, 2015)
In this study, Hermetia illucens (Diptera: Startiomyidae) a decomposer by nature was used as an agent for converting food waste and this process is known as bioconversion. Bioconversion is a transformation process of waste into valuable product using microorganism or higher biota organisms. In this study, waste reduction index (WRI), efficiency of conversion of digested food (ECD), growth rate (GR, g. d-1) and survival of the H. illucens larvae were determined. The experiment was designed with three different feed loading of 1, 5 and 25 g and. Food wastes as the feed were supplied to the larvae daily. The highest waste reduction index (WRI) value was 4.35 ± 0.17 fed with 1 g of feed, followed by 3.91 ± 0.15 with 5 g of feed and the lowest WRI value was 1.98 ± 0.28 fed with 25 g of feed. Growth rate of the larvae was determined with the changes in the biomass per day. The highest larvae biomass gained was achieved at 78.3 wt feeding with 25 g of food waste. The one-way ANOVA showed the significant difference between the mean larvae biomass with different loading (P < 0.05; F = 15.82; d.f = 2, 48). We conclude that, food waste fed is a suitable feed for the larvae proliferation and at the same time successfully reduces the waste. © 2015, Journal of Pure and Applied Microbiology. All rights reserved.